A high-toughness aluminum foil blank for a battery and a method of manufacturing the same

CN122706996BActive Publication Date: 2026-10-23新星轻合金材料(洛阳)有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611208626.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-23
Estimated Expiration
2046-08-11

AI Technical Summary

Technical Problem

但该方案主要侧重于改善材料的导电、导热及晶粒组织性能,对铝箔坯料在后续复杂电化学使用环境下的耐蚀稳定性考虑相对有限,在韧性、导电性和耐电化学腐蚀性能协同提升方面仍有进一步优化空间

Benefits of technology

本发明采用多孔CeO2负载MWCNT和LaB6,并通过铝包覆改善复合材料与铝熔体的润湿性和相容性,减少团聚、漂浮和夹杂,使其均匀分散于铝基体中。CeO2可作为稳定界面调控点,降低局部电化学腐蚀敏感性;MWCNT和LaB6可形成局部导电桥接,改善导电性并缓解硬脆相引起的应力集中。同时,本发明制备的铌/锆改性钛硼中间合金中,TiB2和Al3Ti可促进α-Al异质形核,Nb、Zr能够提高细化相稳定性,减少细化衰退,并形成细小弥散相钉扎晶界、抑制晶粒粗化。上述作用协同提高铝箔坯料的组织均匀性、韧性、导电性和耐电化学腐蚀能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122706996B_ABST
    Figure CN122706996B_ABST
Patent Text Reader

Abstract

The application provides a high-toughness aluminum foil blank for a battery and a preparation method thereof, and belongs to the technical field of aluminum alloys. The method comprises the following steps: S1, preparing aluminum-coated CeO2 / MWCNT / LaB6; S2, preparing niobium / zirconium modified titanium-boron intermediate alloy; S3, melting high-purity aluminum ingot, adding Al-20Fe intermediate alloy and Al-20Si intermediate alloy, and skimming slag; then adding the niobium / zirconium modified titanium-boron intermediate alloy for stirring, and then cooling and adding the aluminum-coated CeO2 / MWCNT / LaB6 for continuous stirring; and through refining, standing, skimming slag, filtering, casting cooling and surface milling, an aluminum alloy cast ingot is obtained; and S4, after the aluminum alloy cast ingot is subjected to homogenization treatment, the aluminum alloy cast ingot is subjected to hot rolling, cold rolling and intermediate annealing treatment, and is wound to obtain the high-toughness aluminum foil blank for a battery. The application can improve the toughness of the aluminum foil blank while having certain electrical conductivity and electrochemical corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy technology, specifically to a high-toughness aluminum foil blank for batteries and its preparation method. Background Technology

[0002] Aluminum foil materials have advantages such as light weight, high ductility, low cost, and ease of rolling, and are often used in energy storage devices such as lithium-ion batteries, sodium-ion batteries, and supercapacitors. As the requirements for high energy density, long life and high safety of power batteries and energy storage batteries continue to increase, aluminum foil blanks not only need to have good conductivity, but also high toughness.

[0003] Existing aluminum foil blanks for batteries are typically based on industrial pure aluminum or low-alloy aluminum, prepared through processes such as melt refining, filtration, casting, homogenization, and rolling annealing. While these aluminum foil blanks can meet general conductivity and processing performance requirements, they still have certain shortcomings in actual production and use. On the one hand, during the solidification of the aluminum melt, coarse columnar crystals, uneven grain size, and dendritic segregation are easily formed. This leads to insufficient deformation coordination during subsequent rolling, easily causing problems such as edge cracks, microcracks, pinholes, and band breaks, affecting the rolling toughness of the aluminum foil blank. On the other hand, impurity elements such as Fe and Si easily form needle-like or coarse blocky second phases, which can easily become crack initiation sources during rolling deformation and may also induce localized galvanic corrosion, reducing the stability of the aluminum foil in the electrolyte environment.

[0004] Patent application CN112030014A discloses an aluminum alloy material for power batteries, its preparation method, and its application. It eliminates the influence of harmful impurities by adding specific rare earth elements and uses a novel Al-Re-B grain refinement technology to eliminate the adverse effects of Ti on conductivity in traditional grain refiners. However, this approach primarily focuses on improving the material's electrical and thermal conductivity and grain structure, with relatively limited consideration for the corrosion resistance stability of the aluminum foil blank under subsequent complex electrochemical operating environments. Further optimization is still needed in synergistically improving toughness, conductivity, and electrochemical corrosion resistance.

[0005] Therefore, there is a need to provide a high-toughness aluminum foil blank for batteries and its preparation method to solve the above-mentioned technical problems. Summary of the Invention

[0006] In view of this, the present invention provides a high-toughness aluminum foil blank for batteries and a method for preparing the same, which can improve the toughness of the aluminum foil blank while having certain conductivity and resistance to electrochemical corrosion.

[0007] To achieve the above objectives, the present invention provides a method for preparing a high-toughness aluminum foil blank for batteries, comprising the following steps:

[0008] S1. Add porous CeO2 material to MWCNT dispersion, sonicate, then add LaB6 and sonicate, stir, and dry to obtain porous CeO2 / MWCNT / LaB6 composite material. Further add to anhydrous ethanol and sonicate, add nitrogen atomized aluminum powder and stir, dry, ball mill, cold press and heat treat to obtain aluminum coated CeO2 / MWCNT / LaB6. S2. After melting high-purity aluminum ingots, Al-10Nb master alloy, Al-10Zr master alloy, Al-5Ti-1B master alloy and Al-10Ti master alloy are added, stirred and melted and kept at a constant temperature. After refining, slag removal and casting cooling, niobium / zirconium modified titanium boron master alloy is obtained. S3. After melting high-purity aluminum ingots, add Al-20Fe master alloy and Al-20Si master alloy, and remove slag; then add niobium / zirconium modified titanium boron master alloy and stir, then cool down and add aluminum-coated CeO2 / MWCNT / LaB6 and continue stirring. After refining, settling, removing slag, filtering, casting and cooling and surface milling, aluminum alloy ingot is obtained. S4. After homogenization treatment, aluminum alloy ingots are hot rolled, cold rolled and intermediate annealed, and then coiled to obtain high-toughness aluminum foil blanks for batteries.

[0009] This invention improves the dispersion stability of MWCNTs and LaB6 by using porous CeO2 material as a loading framework, reducing the risk of agglomeration, floating, and inclusion formation when directly added to molten aluminum. The outer aluminum coating layer improves the wettability and compatibility between the composite material and the molten aluminum, allowing it to be more uniformly dispersed in the aluminum matrix. CeO2 has good chemical stability and can serve as a stable rare earth oxide interface control point, improving the interface stability between the aluminum matrix and the second phase, and reducing interface defects and localized electrochemical corrosion susceptibility. MWCNTs have good electron transport capabilities and can form a locally conductive bridging structure between CeO2, LaB6, and the aluminum matrix, improving the conductivity of the aluminum foil blank. LaB6 has good chemical stability and metallic conductivity, which can compensate for the insufficient conductivity of CeO2 and help reduce stress concentration and localized electrochemical corrosion susceptibility caused by coarse, hard, and brittle phases, thereby improving the toughness, conductivity, and electrochemical corrosion resistance of the aluminum foil blank.

[0010] In the niobium / zirconium modified titanium-boron master alloy prepared by this invention, TiB2 and Al3Ti can serve as heterogeneous nucleation cores for α-Al, promoting grain refinement in the as-cast state. Nb and Zr can modify the interface of TiB2 particles, improving their nucleation activity and thermal stability, and reducing the problems of easy agglomeration, sedimentation, and grain refinement degradation of traditional Al-Ti-B refining agents. At the same time, Ti, Nb, and Zr are conducive to the formation of fine and dispersed Al3(Ti,Nb,Zr) phases during subsequent heat treatment, which have a pinning effect on grain boundaries and subgrain boundaries, inhibiting grain coarsening, thereby improving the microstructure uniformity and toughness of the aluminum foil blank.

[0011] Optionally, the porous CeO2 material is obtained by mixing a cerium salt solution with an organic ligand solution, ultrasonically treating for 30-40 min, then transferring it to a stainless steel reactor lined with polytetrafluoroethylene, reacting at 100-120℃ for 18-20 h, cooling to room temperature, centrifuging to collect the precipitate, washing it 3-5 times with deionized water and anhydrous ethanol, drying it at 50-60℃ for 8-10 h, then placing it in a muffle furnace, heating it to 500-550℃ at 3℃ / min in air atmosphere, holding it at that temperature for 2-3 h, and cooling it to room temperature; the MWCNT dispersion is obtained by adding carboxylated multi-walled carbon nanotubes to anhydrous ethanol and ultrasonically dispersing for 30-50 min.

[0012] This invention forms a cerium-based MOF precursor through the coordination self-assembly reaction of cerium salt and organic ligands, and then decomposes the organic framework by air calcination and transforms it into a porous CeO2 material. This gives CeO2 a high specific surface area and many interfacial active sites, which is beneficial for subsequent loading of MWCNT and LaB6, reduces their agglomeration, and improves the dispersion stability and interfacial bonding effect of the composite material.

[0013] Optionally, the cerium salt solution is obtained by adding 4.5-5 parts by mass of Ce(NO3)3·6H2O to 50-60 parts by mass of deionized water / DMF mixed solvent and stirring for 20-30 min; the organic ligand solution is obtained by adding 0.8-1.2 parts by mass of 1,3,5-benzenetricarboxylic acid to 25-30 parts by mass of anhydrous ethanol and stirring for 30-40 min; the volume ratio of deionized water to DMF in the deionized water / DMF mixed solvent is 1:1; the MWCNT dispersion comprises the following raw materials in parts by mass: 0.005-0.01 parts by mass of carboxylated multi-walled carbon nanotubes and 10 parts by mass of anhydrous ethanol.

[0014] Optionally, in step S1, 1.6-1.8 parts by weight of porous CeO2 material are added to the MWCNT dispersion and ultrasonically dispersed for 30-50 minutes. Then, 0.08-0.1 parts by weight of LaB6 are added and ultrasonically dispersed for another 20-30 minutes. The mixture is stirred for 2-3 hours and dried at 60-65°C for 8-10 hours to obtain a porous CeO2 / MWCNT / LaB6 composite material. Further, 20-25 parts by weight of non-woven fabric are added... The aluminum powder was ultrasonically dispersed in aqueous ethanol for 10-20 min, then 7.5-8.5 parts by weight of nitrogen-atomized aluminum powder were added and stirred for 30-60 min. After drying at 60-65℃ for 6-8 h, the powder was ball-milled at 120-150 r / min for 0.5-1 h under argon protection, then cold-pressed under 100 MPa pressure, and held at 300-320℃ for 1-1.5 h under argon atmosphere to obtain aluminum-coated CeO2 / MWCNT / LaB6.

[0015] Low-speed ball milling under argon protection reduces the oxidation of aluminum powder and MWCNT during the mixing process, while avoiding significant damage to the porous CeO2 structure and the tubular structure of MWCNT caused by high-energy ball milling. This allows nitrogen-atomized aluminum powder to be distributed on the surface of the CeO2 / MWCNT / LaB6 composite material through mechanical interlocking, surface adhesion, and interparticle compaction, forming a mechanical coating layer of aluminum powder. Subsequent heat treatment under argon atmosphere can further remove residual solvents and improve the bonding strength between aluminum powders and between aluminum powder and the composite material.

[0016] Optionally, in step S2, high-purity aluminum ingots are added to a graphite crucible and heated to 760°C to melt. After slag removal, the temperature is raised to 820-850°C, and Al-10Nb master alloy, Al-10Zr master alloy, Al-5Ti-1B master alloy, and Al-10Ti master alloy are added sequentially. The mixture is mechanically stirred at 400 r / min for 20-30 min, then held at 800-850°C for 30-50 min, and then refined with argon gas for 8-10 min. After slag removal, the mixture is poured into a metal mold preheated to 250°C and cooled to obtain niobium / zirconium modified titanium-boron master alloy.

[0017] Optionally, the niobium / zirconium modified titanium-boron master alloy comprises the following raw materials in parts by weight: 2-2.5 parts high-purity aluminum ingot, 0.7-1 parts Al-10Nb master alloy, 0.7-1 parts Al-10Zr master alloy, 4-5 parts Al-5Ti-1B master alloy and 0.3-0.5 parts Al-10Ti master alloy.

[0018] Optionally, in step S3, high-purity aluminum ingots are added to a melting furnace and melted at 730~750℃. Then, Al-20Fe master alloy and Al-20Si master alloy are added, and slag is removed. The melt temperature is controlled at 750~760℃, and niobium / zirconium modified titanium-boron master alloy is added. The mixture is stirred at 350r / min for 10~15min. The melt temperature is then lowered to 730~740℃, and aluminum-coated CeO2 / MWCNT / LaB6 preheated to 200℃ is added. The mixture is stirred for 8~10min, and argon gas is introduced for refining for 10~15min. The mixture is allowed to stand for 8~10min, and slag is removed. The mixture is filtered through a 20~30ppi ceramic foam filter plate and poured into a pre-dried water-cooled copper mold for cooling and shaping. After demolding, the oxide layer and surface segregation layer on the upper and lower surfaces of the ingot are milled off to obtain an aluminum alloy ingot.

[0019] This invention incorporates preheated aluminum-coated CeO2 / MWCNT / LaB6 at 200°C to reduce the risk of temperature shock, splashing, and gas absorption when added to the melt, and to improve its wetting and dispersibility in the molten aluminum. In addition, milling off the oxide layer and surface segregation layer on the upper and lower surfaces of the billet can remove oxide inclusions, coarse grains on the surface, and compositional segregation areas, thereby reducing subsequent hot rolling cracks, pinholes, and surface defects, and improving the rolling stability of the billet.

[0020] Optionally, the aluminum alloy ingot comprises the following raw materials in parts by weight: 95-98 parts high-purity aluminum ingot, 2.2-2.5 parts Al-20Fe master alloy, 0.5-0.7 parts Al-20Si master alloy, 0.25-0.4 parts niobium / zirconium modified titanium-boron master alloy, and 0.12-0.15 parts aluminum-coated CeO2 / MWCNT / LaB6.

[0021] Optionally, in step S4, the aluminum alloy ingot is placed in a heating furnace and held at 500-550℃ for 8-10 hours, then cooled to 430-460℃ and held for 2.5-3.5 hours. Afterward, the temperature is raised to 470-480℃ and held for 30-40 minutes, followed by 4-6 passes of hot rolling. The initial rolling temperature is 470-480℃. After hot rolling to a thickness of 8.0-9.0 mm, the ingot is held at 320-350℃ for 0.5-1 hour, followed by 2-3 passes of hot rolling. The thickness is 6.0~6.8mm, and the final rolling temperature is 300~350℃; then it is held at 260~280℃ for 3~4h, cooled, and a hot-rolled aluminum alloy strip billet is obtained; the hot-rolled aluminum alloy strip billet is cold-rolled 8~10 times to a thickness of 0.30~0.35mm; then it is intermediate annealed at 300~350℃ for 2~3h, and then cold-rolled 3~4 times to a thickness of 0.20~0.25mm, and coiled to obtain a high-toughness aluminum foil billet for batteries.

[0022] The present invention performs a short-term intermediate recovery treatment at 320~350℃ after hot rolling to an intermediate thickness, which is beneficial to the moderate recovery and rearrangement of high-density dislocations generated by hot rolling deformation, releases some deformation stress, and reduces the tendency of local stress concentration and crack initiation in subsequent rolling, thereby further improving the toughness of aluminum foil blanks for batteries.

[0023] The present invention also provides a high-toughness aluminum foil blank for batteries, which is prepared by the above-described preparation method.

[0024] The high-toughness aluminum foil blank prepared by the above method has high rolling toughness, good electrical conductivity and electrochemical corrosion resistance, and can be used for subsequent cold rolling and precision rolling to prepare aluminum foil for batteries.

[0025] The above-described technical solution of the present invention has at least the following beneficial effects: This invention employs porous CeO2-loaded MWCNTs and LaB6, and improves the wettability and compatibility of the composite material with the aluminum melt through aluminum coating, reducing agglomeration, floating, and inclusions, and ensuring uniform dispersion within the aluminum matrix. CeO2 acts as a stabilizing interface control point, reducing localized electrochemical corrosion susceptibility; MWCNTs and LaB6 form localized conductive bridges, improving conductivity and alleviating stress concentration caused by hard and brittle phases. Simultaneously, in the niobium / zirconium-modified titanium-boron master alloy prepared in this invention, TiB2 and Al3Ti promote α-Al heterogeneous nucleation, while Nb and Zr enhance the stability of the refining phase, reduce refining degradation, and form fine, dispersed phases that pin grain boundaries and inhibit grain coarsening. These effects synergistically improve the microstructure uniformity, toughness, conductivity, and electrochemical corrosion resistance of the aluminum foil blank. Attached Figure Description

[0026] Figure 1 This is a SEM image of the sample obtained in Example 1 of this invention after an accelerated electrochemical corrosion simulation test; Figure 2 This is a SEM image of the sample obtained in Comparative Example 1 of this invention after an accelerated electrochemical corrosion simulation test. Figure 3 This is a SEM image of the sample obtained in Comparative Example 3 of this invention after an accelerated electrochemical corrosion simulation test. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are some embodiments of the present invention, and all other embodiments obtained by those skilled in the art based on the described embodiments of the present invention are within the scope of protection of the present invention.

[0028] The carboxylated multi-walled carbon nanotubes used in the following examples have a particle size of 10-20 nm; nitrogen-atomized aluminum powder has a particle size of 20-30 μm; and LaB6 has a particle size of 100-200 nm.

[0029] Example 1 4.8 parts of Ce(NO3)3·6H2O were added to 55 parts of a deionized water / DMF mixed solvent (the volume ratio of deionized water to DMF was 1:1) and stirred for 25 min to obtain a cerium salt solution; 1.0 part of 1,3,5-benzenetricarboxylic acid was added to 28 parts of anhydrous ethanol and stirred for 35 min to obtain an organic ligand solution; the cerium salt solution and the organic ligand solution were mixed and sonicated for 35 min, then transferred to a stainless steel reactor lined with polytetrafluoroethylene and reacted at 110 °C for 19 h. After cooling to room temperature, the precipitate was collected by centrifugation, washed four times with deionized water and anhydrous ethanol, dried at 55 °C for 9 h, and then placed in a muffle furnace. The temperature was increased to 530 °C at 3 °C / min under air atmosphere and calcined for 2.5 h. After cooling to room temperature, porous CeO2 material was obtained; 0.008 parts of carboxylated multi-walled carbon nanotubes were added to 10 parts of anhydrous ethanol and sonicated for 40 min to obtain a MWCNT dispersion.

[0030] 1.7 parts of porous CeO2 material were added to MWCNT dispersion and ultrasonically dispersed for 40 min. Then, 0.09 parts of LaB6 were added and ultrasonically dispersed for another 25 min. The mixture was stirred for 2.5 h and dried at 62 °C for 9 h to obtain a porous CeO2 / MWCNT / LaB6 composite material. This composite material was then further added to 22 parts of anhydrous ethanol and ultrasonically dispersed for 15 min. 8.0 parts of nitrogen-atomized aluminum powder were added and stirred for 45 min. After drying at 62 °C for 7 h, the mixture was ball-milled at 135 r / min for 0.8 h under argon protection. Finally, it was cold-pressed at 100 MPa and held at 310 °C for 1.2 h under argon atmosphere to obtain aluminum-coated CeO2 / MWCNT / LaB6.

[0031] 2.2 parts of high-purity aluminum ingot (purity ≥99.95%) were added to a graphite crucible and heated to 760℃ to melt. After slag removal, the temperature was raised to 835℃, and 0.85 parts of Al-10Nb master alloy, 0.85 parts of Al-10Zr master alloy, 4.5 parts of Al-5Ti-1B master alloy, and 0.4 parts of Al-10Ti master alloy were added in sequence. The mixture was mechanically stirred at 400 r / min for 25 min, then held at 830℃ for 40 min, and then refined with argon gas for 9 min. After slag removal, the mixture was poured into a metal mold preheated to 250℃ and cooled to obtain niobium / zirconium modified titanium boron master alloy.

[0032] 96.5 parts of high-purity aluminum ingots (purity ≥99.95%) were added to a melting furnace and melted at 740℃. Then, 2.35 parts of Al-20Fe master alloy and 0.6 parts of Al-20Si master alloy were added, and the slag was removed. The melt temperature was controlled at 755℃, and 0.32 parts of niobium / zirconium modified titanium boron master alloy were added. The mixture was stirred at 350 r / min for 12 min. The melt temperature was then reduced to 735℃, and 0.13 parts of aluminum-coated CeO2 / MWCNT / LaB6 preheated to 200℃ were added. The mixture was stirred for 9 min, and argon gas was introduced for refining for 12 min. The mixture was allowed to stand for 9 min, and the slag was removed. The mixture was filtered through a 25 ppi ceramic foam filter plate and poured into a pre-dried water-cooled copper mold to cool and solidify. After demolding, the oxide layer and surface segregation layer on the upper and lower surfaces of the ingot were milled off to obtain the aluminum alloy ingot.

[0033] The aluminum alloy ingot was placed in a heating furnace and held at 530℃ for 9 hours, then cooled to 450℃ and held for 3 hours. It was then heated to 475℃ and held for 35 minutes before being hot-rolled in 5 passes. The initial rolling temperature was 475℃, and the ingot was hot-rolled to a thickness of 8.5 mm. It was then held at 335℃ for 0.8 hours, followed by 2 passes of hot rolling to a thickness of 6.5 mm, with a final rolling temperature of 325℃. The ingot was then held at 270℃ for 3.5 hours and cooled to obtain a hot-rolled aluminum alloy strip. The hot-rolled aluminum alloy strip was then cold-rolled in 10 passes to a thickness of 0.32 mm. It was then annealed at 335℃ for 2.5 hours, followed by 3 more passes of cold rolling to a thickness of 0.22 mm, and finally coiled to obtain a high-toughness aluminum foil blank for batteries.

[0034] Example 2 4.6 parts of Ce(NO3)3·6H2O were added to 52 parts of a deionized water / DMF mixed solvent (the volume ratio of deionized water to DMF was 1:1) and stirred for 25 min to obtain a cerium salt solution; 0.9 parts of 1,3,5-benzenetricarboxylic acid were added to 26 parts of anhydrous ethanol and stirred for 32 min to obtain an organic ligand solution; the cerium salt solution and the organic ligand solution were mixed and sonicated for 32 min, and then transferred to a stainless steel reactor lined with polytetrafluoroethylene. The reaction was carried out at 105℃ for 18.5 h, cooled to room temperature, and the precipitate was collected by centrifugation. It was washed four times with deionized water and anhydrous ethanol, dried at 52℃ for 8.5 h, and then placed in a muffle furnace. The temperature was increased to 510℃ at 3℃ / min under air atmosphere and calcined for 2.2 h. After cooling to room temperature, porous CeO2 material was obtained. 0.006 parts of carboxylated multi-walled carbon nanotubes were added to 10 parts of anhydrous ethanol and ultrasonically dispersed for 35 min to obtain MWCNT dispersion.

[0035] 1.65 parts of porous CeO2 material were added to MWCNT dispersion and ultrasonically dispersed for 35 min. Then, 0.085 parts of LaB6 were added and ultrasonically dispersed for another 22 min. The mixture was stirred for 2.2 h and dried at 62 °C for 8.5 h to obtain a porous CeO2 / MWCNT / LaB6 composite material. This composite material was then further added to 21 parts of anhydrous ethanol and ultrasonically dispersed for 12 min. 7.8 parts of nitrogen-atomized aluminum powder were added and stirred for 40 min. After drying at 62 °C for 6.5 h, the mixture was ball-milled at 130 r / min for 0.6 h under argon protection. Finally, it was cold-pressed under 100 MPa pressure and held at 305 °C for 1.2 h under argon atmosphere to obtain aluminum-coated CeO2 / MWCNT / LaB6.

[0036] 2.1 parts of high-purity aluminum ingot (purity ≥99.95%) were added to a graphite crucible and heated to 760℃ to melt. After slag removal, the temperature was raised to 830℃, and 0.8 parts of Al-10Nb master alloy, 0.8 parts of Al-10Zr master alloy, 4.2 parts of Al-5Ti-1B master alloy, and 0.35 parts of Al-10Ti master alloy were added in sequence. The mixture was mechanically stirred at 400 r / min for 22 min, then held at 815℃ for 35 min, and then refined with argon gas for 8.5 min. After slag removal, the mixture was poured into a metal mold preheated to 250℃ and cooled to obtain niobium / zirconium modified titanium boron master alloy.

[0037] 96 parts of high-purity aluminum ingots (purity ≥99.95%) were added to a melting furnace and melted at 735℃. Then, 2.3 parts of Al-20Fe master alloy and 0.55 parts of Al-20Si master alloy were added, and the slag was removed. The melt temperature was controlled at 752℃, and 0.3 parts of niobium / zirconium modified titanium boron master alloy were added. The mixture was stirred at 350 r / min for 12 min. The melt temperature was then reduced to 732℃, and 0.12 parts of aluminum-coated CeO2 / MWCNT / LaB6 preheated to 200℃ were added. The mixture was stirred for 8.5 min, and argon gas was introduced for refining for 12 min. The mixture was allowed to stand for 8.5 min, and the slag was removed. The mixture was filtered through a 25 ppi ceramic foam filter plate and poured into a pre-dried water-cooled copper mold to cool and solidify. After demolding, the oxide layer and surface segregation layer on the upper and lower surfaces of the ingot were milled off to obtain the aluminum alloy ingot.

[0038] The aluminum alloy ingot was placed in a heating furnace and held at 520℃ for 8.5 hours, then cooled to 440℃ and held for 2.8 hours. It was then heated to 472℃ and held for 32 minutes before being hot-rolled in 5 passes. The initial rolling temperature was 472℃, and the ingot was hot-rolled to a thickness of 8.2 mm. It was then held at 330℃ for 0.6 hours, followed by 2 passes of hot rolling to a thickness of 6.2 mm, with a final rolling temperature of 315℃. The ingot was then held at 265℃ for 3.2 hours and cooled to obtain a hot-rolled aluminum alloy strip. This strip was then cold-rolled in 10 passes to a thickness of 0.31 mm. Finally, it underwent intermediate annealing at 330℃ for 2.5 hours, followed by 3 more passes of cold rolling to a thickness of 0.22 mm. The strip was then coiled to obtain a high-toughness aluminum foil blank for batteries.

[0039] Example 3 Five parts of Ce(NO3)3·6H2O were added to 60 parts of a deionized water / DMF mixed solvent (the volume ratio of deionized water to DMF was 1:1) and stirred for 30 min to obtain a cerium salt solution. 1.2 parts of 1,3,5-benzenetricarboxylic acid were added to 30 parts of anhydrous ethanol and stirred for 40 min to obtain an organic ligand solution. The cerium salt solution and the organic ligand solution were mixed and sonicated for 40 min. Then, the mixture was transferred to a stainless steel reactor lined with polytetrafluoroethylene and reacted at 120 °C for 20 h. After cooling to room temperature, the precipitate was collected by centrifugation and washed five times with deionized water and anhydrous ethanol, dried at 60 °C for 10 h, and then placed in a muffle furnace. The temperature was increased to 550 °C at 3 °C / min under air atmosphere and calcined for 3 h. After cooling to room temperature, porous CeO2 material was obtained. 0.01 parts of carboxylated multi-walled carbon nanotubes were added to 10 parts of anhydrous ethanol and sonicated for 50 min to obtain a MWCNT dispersion.

[0040] 1.8 parts of porous CeO2 material were added to MWCNT dispersion and ultrasonically dispersed for 50 min. Then, 0.1 parts of LaB6 were added and ultrasonically dispersed for another 30 min. The mixture was stirred for 3 h and dried at 65 °C for 10 h to obtain a porous CeO2 / MWCNT / LaB6 composite material. This composite material was then further added to 25 parts of anhydrous ethanol and ultrasonically dispersed for 20 min. 8.5 parts of nitrogen-atomized aluminum powder were added and stirred for 60 min. After drying at 65 °C for 8 h, the mixture was ball-milled at 150 r / min for 1 h under argon protection. Finally, it was cold-pressed under 100 MPa pressure and held at 320 °C for 1.5 h under argon atmosphere to obtain aluminum-coated CeO2 / MWCNT / LaB6.

[0041] 2.5 parts of high-purity aluminum ingots (purity ≥99.95%) were added to a graphite crucible and heated to 760℃ to melt. After slag removal, the temperature was raised to 850℃, and 1 part of Al-10Nb master alloy, 1 part of Al-10Zr master alloy, 5 parts of Al-5Ti-1B master alloy and 0.5 parts of Al-10Ti master alloy were added in sequence. The mixture was mechanically stirred at 400 r / min for 30 min, then held at 850℃ for 50 min, and then refined with argon gas for 10 min. After slag removal, the mixture was poured into a metal mold preheated to 250℃ and cooled to obtain niobium / zirconium modified titanium boron master alloy.

[0042] 98 parts of high-purity aluminum ingots (purity ≥99.95%) were added to a melting furnace and melted at 750℃. Then, 2.5 parts of Al-20Fe master alloy and 0.7 parts of Al-20Si master alloy were added, and the slag was removed. The melt temperature was controlled at 760℃, and 0.4 parts of niobium / zirconium modified titanium boron master alloy were added. The mixture was stirred at 350 r / min for 15 min. The melt temperature was then reduced to 740℃, and 0.15 parts of aluminum-coated CeO2 / MWCNT / LaB6 preheated to 200℃ were added. The mixture was stirred for 10 min, and argon gas was introduced for refining for 15 min. The mixture was allowed to stand for 10 min, and the slag was removed. The mixture was filtered through a 30 ppi ceramic foam filter plate and poured into a pre-dried water-cooled copper mold to cool and solidify. After demolding, the oxide layer and surface segregation layer on the upper and lower surfaces of the ingot were milled off to obtain the aluminum alloy ingot.

[0043] The aluminum alloy ingot was placed in a heating furnace and held at 550℃ for 10 hours, then cooled to 460℃ and held for 3.5 hours. It was then heated to 480℃ and held for 40 minutes before being hot-rolled in four passes. The initial rolling temperature was 480℃, and the ingot was hot-rolled to a thickness of 9 mm. It was then held at 350℃ for 1 hour, followed by three more passes to a thickness of 6.6 mm, with a final rolling temperature of 350℃. The ingot was then held at 280℃ for 4 hours and cooled to obtain a hot-rolled aluminum alloy strip. This strip was then cold-rolled in eight passes to a thickness of 0.35 mm. Finally, it underwent intermediate annealing at 300℃ for 3 hours, followed by three more passes to a thickness of 0.25 mm, and finally coiled to obtain a high-toughness aluminum foil blank for batteries.

[0044] Example 4 4.5 parts of Ce(NO3)3·6H2O were added to 50 parts of a deionized water / DMF mixed solvent (the volume ratio of deionized water to DMF was 1:1) and stirred for 20 min to obtain a cerium salt solution; 0.8 parts of 1,3,5-benzenetricarboxylic acid were added to 25 parts of anhydrous ethanol and stirred for 30 min to obtain an organic ligand solution; the cerium salt solution and the organic ligand solution were mixed and sonicated for 30 min, then transferred to a stainless steel reactor lined with polytetrafluoroethylene and reacted at 100 °C for 18 h. After cooling to room temperature, the precipitate was collected by centrifugation, washed three times with deionized water and anhydrous ethanol, dried at 50 °C for 8 h, and then placed in a muffle furnace. The temperature was increased to 500 °C at 3 °C / min under air atmosphere and calcined for 2 h. After cooling to room temperature, porous CeO2 material was obtained; 0.005 parts of carboxylated multi-walled carbon nanotubes were added to 10 parts of anhydrous ethanol and sonicated for 30 min to obtain a MWCNT dispersion.

[0045] 1.6 parts of porous CeO2 material were added to MWCNT dispersion and ultrasonically dispersed for 30 min. Then, 0.08 parts of LaB6 were added and ultrasonically dispersed for another 20 min. The mixture was stirred for 2 h and dried at 60 °C for 8 h to obtain a porous CeO2 / MWCNT / LaB6 composite material. This composite material was then further added to 20 parts of anhydrous ethanol and ultrasonically dispersed for 10 min. 7.5 parts of nitrogen-atomized aluminum powder were added and stirred for 30 min. After drying at 60 °C for 6 h, the mixture was ball-milled at 120 r / min for 0.5 h under argon protection. Finally, it was cold-pressed under 100 MPa pressure and held at 300 °C for 1 h under argon atmosphere to obtain aluminum-coated CeO2 / MWCNT / LaB6.

[0046] Two parts of high-purity aluminum ingots (purity ≥99.95%) were added to a graphite crucible and heated to 760℃ to melt. After slag removal, the temperature was raised to 820℃, and 0.7 parts of Al-10Nb master alloy, 0.7 parts of Al-10Zr master alloy, 4 parts of Al-5Ti-1B master alloy, and 0.3 parts of Al-10Ti master alloy were added sequentially. The mixture was mechanically stirred at 400 r / min for 20 min, then held at 800℃ for 30 min, and then refined with argon gas for 8 min. After slag removal, the mixture was poured into a metal mold preheated to 250℃ and cooled to obtain niobium / zirconium modified titanium boron master alloy.

[0047] 95 parts of high-purity aluminum ingots (purity ≥99.95%) were added to a melting furnace and melted at 730℃. Then, 2.2 parts of Al-20Fe master alloy and 0.5 parts of Al-20Si master alloy were added, and the slag was removed. The melt temperature was controlled at 750℃, and 0.25 parts of niobium / zirconium modified titanium boron master alloy were added. The mixture was stirred at 350 r / min for 10 min. The melt temperature was then reduced to 730℃, and 0.13 parts of aluminum-coated CeO2 / MWCNT / LaB6 preheated to 200℃ were added. The mixture was stirred for 8 min, and argon gas was introduced for refining for 10 min. The mixture was allowed to stand for 8 min, and the slag was removed. The mixture was filtered through a 20 ppi ceramic foam filter plate and poured into a pre-dried water-cooled copper mold to cool and solidify. After demolding, the oxide layer and surface segregation layer on the upper and lower surfaces of the ingot were milled off to obtain the aluminum alloy ingot.

[0048] The aluminum alloy ingot was placed in a heating furnace and held at 500℃ for 8 hours, then cooled to 430℃ and held for 2.5 hours. It was then heated to 470℃ and held for 30 minutes before being hot-rolled in 6 passes. The initial rolling temperature was 470℃, and the ingot was hot-rolled to a thickness of 8 mm. It was then held at 320℃ for 0.5 hours, followed by 2 passes of hot rolling to a thickness of 6 mm, with a final rolling temperature of 300℃. The ingot was then held at 260℃ for 3 hours and cooled to obtain a hot-rolled aluminum alloy strip. The hot-rolled aluminum alloy strip was then cold-rolled in 9 passes to a thickness of 0.3 mm. It was then annealed at 320℃ for 2 hours, followed by 4 more passes of cold rolling to a thickness of 0.2 mm, and finally coiled to obtain a high-toughness aluminum foil blank for batteries.

[0049] Example 5 4.9 parts of Ce(NO3)3·6H2O were added to 58 parts of a deionized water / DMF mixed solvent (the volume ratio of deionized water to DMF was 1:1) and stirred for 28 min to obtain a cerium salt solution; 1.1 parts of 1,3,5-benzenetricarboxylic acid were added to 29 parts of anhydrous ethanol and stirred for 38 min to obtain an organic ligand solution; the cerium salt solution and the organic ligand solution were mixed and sonicated for 38 min, and then transferred to a stainless steel reactor lined with polytetrafluoroethylene. The reaction was carried out at 115℃ for 19.5 h, cooled to room temperature, and the precipitate was collected by centrifugation. It was washed five times with deionized water and anhydrous ethanol, dried at 58℃ for 9.5 h, and then placed in a muffle furnace. The temperature was increased to 540℃ at 3℃ / min under air atmosphere and calcined for 2.8 h. After cooling to room temperature, porous CeO2 material was obtained. 0.009 parts of carboxylated multi-walled carbon nanotubes were added to 10 parts of anhydrous ethanol and ultrasonically dispersed for 45 min to obtain MWCNT dispersion.

[0050] 1.75 parts of porous CeO2 material were added to MWCNT dispersion and ultrasonically dispersed for 45 min. Then, 0.095 parts of LaB6 were added and ultrasonically dispersed for another 28 min. The mixture was stirred for 2.8 h and dried at 64 °C for 9.5 h to obtain a porous CeO2 / MWCNT / LaB6 composite material. This composite material was then further added to 24 parts of anhydrous ethanol and ultrasonically dispersed for 18 min. 8.2 parts of nitrogen-atomized aluminum powder were added and stirred for 50 min. After drying at 64 °C for 7.5 h, the mixture was ball-milled at 145 r / min for 0.9 h under argon protection. Finally, it was cold-pressed under 100 MPa pressure and held at 315 °C for 1.4 h under argon atmosphere to obtain aluminum-coated CeO2 / MWCNT / LaB6.

[0051] 2.4 parts of high-purity aluminum ingots (purity ≥99.95%) were added to a graphite crucible and heated to 760℃ to melt. After slag removal, the temperature was raised to 840℃, and 0.9 parts of Al-10Nb master alloy, 0.9 parts of Al-10Zr master alloy, 4.8 parts of Al-5Ti-1B master alloy, and 0.45 parts of Al-10Ti master alloy were added sequentially. The mixture was mechanically stirred at 400 r / min for 28 min, then held at 840℃ for 45 min, and then refined with argon gas for 9.5 min. After slag removal, the mixture was poured into a metal mold preheated to 250℃ and cooled to obtain niobium / zirconium modified titanium boron master alloy.

[0052] 97 parts of high-purity aluminum ingots (purity ≥99.95%) were added to a melting furnace and melted at 745℃. Then, 2.4 parts of Al-20Fe master alloy and 0.65 parts of Al-20Si master alloy were added, and the slag was removed. The melt temperature was controlled at 758℃, and 0.36 parts of niobium / zirconium modified titanium boron master alloy were added. The mixture was stirred at 350 r / min for 14 min. The melt temperature was then reduced to 738℃, and 0.14 parts of aluminum-coated CeO2 / MWCNT / LaB6 preheated to 200℃ were added. The mixture was stirred for 9.5 min, and argon gas was introduced for refining for 14 min. The mixture was allowed to stand for 9.5 min, and the slag was removed. The mixture was filtered through a 30 ppi ceramic foam filter plate and poured into a pre-dried water-cooled copper mold to cool and solidify. After demolding, the oxide layer and surface segregation layer on the upper and lower surfaces of the ingot were milled off to obtain the aluminum alloy ingot.

[0053] The aluminum alloy ingot was placed in a heating furnace and held at 540℃ for 9.5 hours, then cooled to 455℃ and held for 3.2 hours. It was then heated to 478℃ and held for 38 minutes before being hot-rolled in 5 passes. The initial rolling temperature was 478℃, and the ingot was hot-rolled to a thickness of 8.8 mm. It was then held at 345℃ for 0.9 hours, followed by 2 passes of hot rolling to a thickness of 6.8 mm, with a final rolling temperature of 340℃. The ingot was then held at 275℃ for 3.8 hours and cooled to obtain a hot-rolled aluminum alloy strip. This strip was then cold-rolled in 10 passes to a thickness of 0.34 mm. Finally, it underwent intermediate annealing at 340℃ for 3 hours, followed by 3 more passes of cold rolling to a thickness of 0.23 mm. The strip was then coiled to obtain a high-toughness aluminum foil blank for batteries.

[0054] The present invention also includes comparative examples and related experiments.

[0055] Comparative Example 1 Compared with Example 1, the only difference is that aluminum-coated CeO2 / MWCNT / LaB6 was not added. The other preparation steps and components are completely consistent, and a high-toughness aluminum foil blank for batteries is finally obtained.

[0056] Comparative Example 2 Compared with Example 1, the only difference is that a commercially available Al-5Ti-1B master alloy is used instead of the niobium / zirconium modified titanium-boron master alloy. The other preparation steps and compositions are completely consistent, and a high-toughness aluminum foil blank for batteries is finally obtained.

[0057] Comparative Example 3 Compared with Example 1, the only difference is that CeO2 / MWCNT / LaB6 composite material is used instead of aluminum-coated CeO2 / MWCNT / LaB6. The other preparation steps and components are completely consistent, and the high-toughness aluminum foil blank for batteries is finally obtained.

[0058] Performance testing The performance of the high-toughness aluminum foil blanks for batteries obtained in Examples 1-5 and Comparative Examples 1-3 was tested. Each aluminum foil blank was cut into samples of the same size along the rolling direction. Tensile strength and elongation after fracture were tested according to GB / T22638.11-2023 "Aluminum Foil Test Methods Part 11: Tests of Mechanical Properties"; DC resistance was tested according to GB / T22638.6-2016 "Aluminum Foil Test Methods Part 6: Determination of DC Resistance", and the conductivity was calculated. The test results are shown in Table 1.

[0059] Table 1

[0060] As shown in Table 1, the high-toughness aluminum foil blanks for batteries obtained in Examples 1-5 have a tensile strength of 210-216 MPa, an elongation after fracture of 10.1-11.5%, and an electrical conductivity of 59.7-60.5% IACS. This indicates that the aluminum foil blanks prepared by this invention maintain good toughness and electrical conductivity while possessing high strength. In contrast, Comparative Example 1, which did not add aluminum-coated CeO2 / MWCNT / LaB6, has a significantly lower electrical conductivity than Example 1. Comparative Example 2, which used a commercially available Al-5Ti-1B master alloy instead of the niobium / zirconium modified titanium-boron master alloy, showed a significant decrease in tensile strength and elongation after fracture. Comparative Example 3, which used an uncoated CeO2 / MWCNT / LaB6 composite material, had the lowest tensile strength and elongation after fracture. This indicates that adding uncoated composite materials weakens the strength and toughness of the aluminum foil blank and also has a certain impact on the electrical conductivity.

[0061] Accelerated electrochemical corrosion simulation tests were conducted on the high-toughness aluminum foil blanks for batteries obtained in Examples 1-5 and Comparative Examples 1-3. Each aluminum foil blank was cut into samples of the same size, and the mass m0 before corrosion was recorded. A 3.5 wt% NaCl aqueous solution was used as the corrosion medium, with the aluminum foil blank sample as the anode and the graphite sheet as the cathode, at a corrosion rate of 1 A / dm³. 2 Electrolytic corrosion was performed at the current density for 30 minutes. After corrosion, the sample was removed, rinsed with deionized water, cleaned with anhydrous ethanol, and dried to constant weight. The post-corrosion mass m1 was recorded, the corrosion weight loss rate was calculated, and the corrosion state of the sample surface was observed using SEM (scanning electron microscopy). The formula for calculating the corrosion weight loss rate is as follows: ; The test results are shown in Table 2.

[0062] Table 2

[0063] As shown in Table 2, the corrosion weight loss rate of the high-toughness aluminum foil blanks for batteries obtained in Examples 1-5 was 0.84-1.16%, and no obvious pitting corrosion was observed on the surface after corrosion, indicating that the aluminum foil blanks obtained in this invention have good electrochemical corrosion resistance. Combined with... Figures 1-3 Further SEM images of the samples from Example 1, Comparative Example 1, and Comparative Example 3 after testing show that the surface of the sample from Example 1 still maintains a relatively continuous and smooth rolling texture, and no obvious pitting corrosion was observed. In contrast, Comparative Example 1, without aluminum coating on CeO2 / MWCNT / LaB6, showed a corrosion weight loss rate of 3.82%, and the SEM image showed many corrosion spots and local pitting. Comparative Example 3, using the uncoated CeO2 / MWCNT / LaB6 composite material, had the highest corrosion weight loss rate, and the SEM image showed dense pitting, local corrosion grooves, and erosion areas. This also indicates that the use of the uncoated CeO2 / MWCNT / LaB6 composite material easily forms localized electrochemical corrosion sensitive areas.

[0064] The above are preferred embodiments of the present invention. Those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a high-toughness aluminum foil blank for batteries, characterized in that, Includes the following steps: S1. Add 1.6~1.8 parts by weight of porous CeO2 material to MWCNT dispersion, ultrasonically disperse for 30~50 min, then add 0.08~0.1 parts by weight of LaB6 and continue ultrasonic dispersion for 20~30 min, stir for 2~3 h, and dry at 60~65℃ for 8~10 h to obtain porous CeO2 / MWCNT / LaB6 composite material, further add to 20~25 parts by weight of anhydrous ethanol and ultrasonically disperse for 10~20 min, then add 7.5~8 parts by weight of ethanol. Five parts by mass of nitrogen-atomized aluminum powder were stirred for 30-60 min, dried at 60-65℃ for 6-8 h, ball-milled at 120-150 r / min for 0.5-1 h under argon protection, cold-pressed under 100 MPa pressure, and held at 300-320℃ for 1-1.5 h under argon atmosphere to obtain aluminum-coated CeO2 / MWCNT / LaB6; the MWCNT dispersion was obtained by adding carboxylated multi-walled carbon nanotubes to anhydrous ethanol and ultrasonically dispersing for 30-50 min. S2. After melting high-purity aluminum ingots, Al-10Nb master alloy, Al-10Zr master alloy, Al-5Ti-1B master alloy and Al-10Ti master alloy are added. The mixture is stirred and melted and kept at a constant temperature. After refining, slag removal and casting cooling, niobium / zirconium modified titanium boron master alloy is obtained. The niobium / zirconium modified titanium boron master alloy includes the following raw materials by weight: 2~2.5 parts high-purity aluminum ingot, 0.7~1 parts Al-10Nb master alloy, 0.7~1 parts Al-10Zr master alloy, 4~5 parts Al-5Ti-1B master alloy and 0.3~0.5 parts Al-10Ti master alloy. S3. After melting high-purity aluminum ingots, Al-20Fe master alloy and Al-20Si master alloy are added, and the slag is removed. Then, niobium / zirconium modified titanium boron master alloy is added and stirred. Subsequently, the temperature is lowered and aluminum-coated CeO2 / MWCNT / LaB6 is added and stirred again. After refining, settling, slag removal, filtration, casting, cooling, and surface milling, an aluminum alloy ingot is obtained. The aluminum alloy ingot includes the following parts by weight of raw materials: 95~98 parts of high-purity aluminum ingot, 2.2~2.5 parts of Al-20Fe master alloy, 0.5~0.7 parts of Al-20Si master alloy, 0.25~0.4 parts of niobium / zirconium modified titanium boron master alloy, and 0.12~0.15 parts of aluminum-coated CeO2 / MWCNT / LaB6. S4. After homogenization treatment, aluminum alloy ingots are hot rolled, cold rolled and intermediate annealed, and then coiled to obtain high-toughness aluminum foil blanks for batteries.

2. The method for preparing a high-toughness aluminum foil blank for batteries according to claim 1, characterized in that, The porous CeO2 material is prepared by mixing a cerium salt solution with an organic ligand solution, ultrasonically treating for 30-40 min, then transferring it to a stainless steel reactor lined with polytetrafluoroethylene, reacting at 100-120℃ for 18-20 h, cooling to room temperature, centrifuging to collect the precipitate, washing it 3-5 times with deionized water and anhydrous ethanol, drying it at 50-60℃ for 8-10 h, then placing it in a muffle furnace, heating it to 500-550℃ at 3℃ / min in air atmosphere, holding it at that temperature for 2-3 h, and cooling it to room temperature.

3. The method for preparing a high-toughness aluminum foil blank for batteries according to claim 2, characterized in that, The cerium salt solution is obtained by adding 4.5-5 parts by mass of Ce(NO3)3·6H2O to 50-60 parts by mass of deionized water / DMF mixed solvent and stirring for 20-30 min; the organic ligand solution is obtained by adding 0.8-1.2 parts by mass of 1,3,5-benzenetricarboxylic acid to 25-30 parts by mass of anhydrous ethanol and stirring for 30-40 min; the volume ratio of deionized water to DMF in the deionized water / DMF mixed solvent is 1:1; the MWCNT dispersion comprises the following raw materials in parts by mass: 0.005-0.01 parts by mass of carboxylated multi-walled carbon nanotubes and 10 parts by mass of anhydrous ethanol.

4. The method for preparing a high-toughness aluminum foil blank for batteries according to claim 1, characterized in that, In step S2, high-purity aluminum ingots are added to a graphite crucible and heated to 760°C to melt. After slag removal, the temperature is raised to 820-850°C, and Al-10Nb master alloy, Al-10Zr master alloy, Al-5Ti-1B master alloy, and Al-10Ti master alloy are added sequentially. The mixture is mechanically stirred at 400 r / min for 20-30 min, then held at 800-850°C for 30-50 min, and then refined with argon gas for 8-10 min. After slag removal, the mixture is poured into a metal mold preheated to 250°C and cooled to obtain niobium / zirconium modified titanium-boron master alloy.

5. The method for preparing a high-toughness aluminum foil blank for batteries according to claim 1, characterized in that, In step S3, high-purity aluminum ingots are added to a melting furnace and melted at 730-750°C. Al-20Fe master alloy and Al-20Si master alloy are then added, and slag is removed. The melt temperature is controlled at 750-760°C, and niobium / zirconium modified titanium-boron master alloy is added. The mixture is stirred at 350 r / min for 10-15 min. The melt temperature is then lowered to 730-740°C, and aluminum-coated CeO2 / MWCNT / LaB6 preheated to 200°C is added. The mixture is stirred for 8-10 min, and argon gas is introduced for refining for 10-15 min. The mixture is allowed to stand for 8-10 min, and slag is removed. The mixture is then filtered through a 20-30 ppi ceramic foam filter plate and poured into a pre-dried water-cooled copper mold for cooling and shaping. After demolding, the oxide layer and surface segregation layer on the upper and lower surfaces of the ingot are milled off to obtain an aluminum alloy ingot.

6. The method for preparing a high-toughness aluminum foil blank for batteries according to claim 1, characterized in that, In step S4, the aluminum alloy ingot is placed in a heating furnace and held at 500-550℃ for 8-10 hours, then cooled to 430-460℃ and held for 2.5-3.5 hours. Afterward, the temperature is raised to 470-480℃ and held for 30-40 minutes, followed by 4-6 passes of hot rolling. The initial rolling temperature is 470-480℃. After hot rolling to a thickness of 8.0-9.0 mm, the ingot is held at 320-350℃ for 0.5-1 hour, followed by 2-3 passes of hot rolling to a thickness of... The thickness is 6.0~6.8mm, and the final rolling temperature is 300~350℃; then it is held at 260~280℃ for 3~4h, cooled, and a hot-rolled aluminum alloy strip billet is obtained; the hot-rolled aluminum alloy strip billet is cold-rolled in 8~10 passes to a thickness of 0.30~0.35mm; then it is intermediate annealed at 300~350℃ for 2~3h, and then cold-rolled in 3~4 passes to a thickness of 0.20~0.25mm, and coiled to obtain a high-toughness aluminum foil billet for batteries.

7. A high-toughness aluminum foil blank for batteries, characterized in that, It is prepared using the method for preparing a high-toughness aluminum foil blank for batteries according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Aluminum alloy material for power battery and preparation method and application thereof

    CN112030014A

  • Aluminium alloy foil for lithium ion battery positive current collector and manufacturing method thereof

    CN102787259A

  • Lens barrel made of glass fiber reinforced resin composition

    JP2010015091A